Implementasi Kebijakan Kepegawaian Melalui Aplikasi Analisis Beban Kerja (E-ABK) Pada Kantor Kecamatan Bubutan Kota Surabaya - Willyanto, Andre; Muljanto, Muhammad Agus (MES Bogor, 2024)
This study aims to analyze the implementation of personnel policies through Workload Analysis (E-ABK) at the Bubutan District office, Surabaya City. The research method used is qualitative descriptive with data collection through interviews, observations, and documentation. The results of the study show that there are several obstacles in the implementation of E-ABK, including the lack of effective communication between the Bubutan District office of Surabaya and the Organization Section of the Regional Secretariat of Surabaya, limited resources that there are still employees who have difficulty filling in supporting data, especially elderly employees, so there is a need for a mentoring role given to users of the E-ABK application, as well as the attitude and disposition of employees showing dissatisfaction in the use of the E-ABK application. In addition, the complex bureaucratic structure is also an obstacle in filling out E-ABK. To overcome these obstacles, it is recommended to increase communication and socialization regarding E-ABK, provide adequate resource support, provide motivation and appreciation to employees, simplify bureaucratic structure, and develop E-ABK. Better implementation is expected to increase the efficiency and effectiveness of employee workload management and achieve organizational goals more optimally.